Changes in the chemical characteristics of acid sulfate soil applied to oyster mushroom baglog waste compost - Ahmad Wahyudianur; Jumar Jumar; Tuti Heiriyani; Riza Adrianoor Saputra; Nukhak Nufita Sari (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2022)
Acid sulfate soils are one of the potential lands for agriculture with appropriate treatment. The main problem in these soils is the chemical properties, which is high in acidity and limited nutrients availability and Fe and Al toxicity. Amelioration techniques are needed to improve the chemical properties of the soil, which is oyster mushroom baglog waste compost. This research aims to study the effect of oyster mushroom baglog waste (OMBW) compost to soil chemical properties, also to know the best dosage which affects chemical properties. The research was conducted at the greenhouse of the Agroecotechnology Department and the Laboratory of the Soil Department, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The research was started from August-October 2020. One-factor completely randomized design (CRD) with five treatments and five replications was used, the b0 treatment was not OMBW compost, b1 was 5 t ha-1, b2 was 10 t ha-1, b3 was 15 t ha-1, and b4 was 20 t ha-1. The application of the OMBW compost significantly affected the soil pH and decreased soluble-Fe and Al, but did not significantly affect the Eh value at 2 WAA (Week After Application). The best concentration of dose of OMBW compost was 10 t ha-1 which improved soil pH, decreased soluble-Fe and Al.